Optimizing Google Classroom User Behaviour: An Integrated Analysis Using TAM and TPB Models - Edy Suryanto; Nina Oktarina; Tusyanah Tusyanah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Google classroom as one of the learning platforms has been popularly used. This study aims to examine the determinants of user behavior by testing perceived ease of use variables, perceived usefulness, and subjective norm as a predictor of intention and actual control as moderation of intention-to-behavior relationship. The population in this study are 108  students in vocational high school. This study uses survey techniques or saturated samples. Data collection in this study using questionnaires. The analysis method used is a structural equation model (SEM) with SmartPLS 3.0 analysis tool. The study results found that perceived ease of use, perceived usefulness, and subjective norm are predictors of behavioral intentions with a value of R2 0.783 or 78.3%. Behavior intention predicts user behavior with R2 0.647 or 64.7%. Actual control succeeded in moderating the relationship of behavior intention to and use behavior. According to the study's results, students' behavioral intention to use Google Classroom was predicted by the Perceived Ease of Use, Perception of Usefulness, and Subject Norm. Actual behavior control can strengthen student use behavior of students using Google Classroom. The students will have a strong intention to use Google Classroom when they have actual control over themselves.